Evaluation of a Novel MALDI Biotyper Algorithm to Distinguish Mycobacterium intracellulare From Mycobacterium chimaera - Epperson, L. Elaine; Timke, Markus; Hasan, Nabeeh A.; Godo, Paul; Durbin, David; Helstrom, Niels K.; Shi, Gongyi; Kostrzewa, Markus; Strong, Michael; Salfinger, Max (Frontiers in Microbiology, 2018)
Accurate and timely mycobacterial species identification is imperative for successful diagnosis, treatment, and management of disease caused by nontuberculous mycobacteria (NTM). The current most widely utilized method for NTM species identification is Sanger sequencing of one or more genomic loci, followed by BLAST sequence analysis. MALDI-TOF MS offers a less expensive and increasingly accurate alternative to sequencing, but the commercially available assays used in clinical mycobacteriology cannot differentiate between Mycobacterium intracellulare and Mycobacterium chimaera, two closely-related potentially pathogenic species of NTM that are members of the Mycobacterium avium complex (MAC). Because this differentiation of MAC species is challenging in a diagnostic setting, Bruker has developed an improved spectral interpretation algorithm to differentiate M. chimaera and M. intracellulare based on differential spectral peak signatures. Here, we utilize a set of 185 MAC isolates that have been characterized using rpoB locus sequencing followed by whole genome sequencing in some cases, to test the accuracy of the Bruker subtyper software to identify M. chimaera (n=49) and M. intracellulare (n=55). 100% of the M. intracellulare and 82% of the M. chimaera isolates were accurately identified using the MALDI Biotyper algorithm. This subtyper module is available with the MALDI Biotyper Compass software and offers a promising mechanism for rapid and inexpensive species determination for M. chimaera and M. intracellulare.